Study on damping characteristics of steam turbine hollow vane with damper - Yasutomo KANEKO; Makoto TOMITA; Hiroyuki YAMASHITA; Hiroharu OOYAMA (Nihon Kikai Gakkai ronbunshu, 2014)
A vane used in a low pressure end of steam turbine is usually fixed to a shroud and a casing by welding both ends. In such a vane structure, the damping in loading operation is comprised of the material damping and the aerodynamic damping, because the structural damping is very small. Recently, in order to increase the reliability of a steam turbine vane, a hollow vane with a friction damper has been used. In this paper, for the purpose of clarifying the damping characteristics of the hollow vane with a friction damper, first, the excitation test of the model vane is carried out. Second, the analysis method for predicting the damping characteristics of the hollow vane with a friction damper is proposed. The validity of the analysis method is verified by comparing the measured damping characteristics of the vane with the calculated ones. Finally, the analysis of the actual steam turbine hollow vane with a friction damper is also carried out. From these results, the damping characteristics of the hollow vane with a friction damper are clarified.